PENANAMAN SIKAP NASIONALISME MELALUI MATA PELAJARAN IPS PADA SISWA KELAS IV SDN 05 V SUKU BAWAH - Sagita, Geni; Supriatna, Encep (Didaktika, 2021)
The entry of the current era of globalization impacts the decline in the value of the individual towards his love for the homeland. One of the efforts to filter the influence of the entry of foreign cultures into Indonesia is by instilling an attitude of nationalism in students. This study aims to determine the form of nationalism, cultivate a nationalistic mindset, and know the supporting and inhibiting factors inculcating nationalism through social studies subjects in IV grade students of SDN 05 Suku Bawah. In conducting this research, the researcher uses a qualitative descriptive method with a naturalistic inquiry strategy. In this method, the researcher goes directly to the field, observing the subject and exploring the problems. The research is carried out purely without manipulating the subject to be studied. This research was conducted at SDN 05 V Suku Bawah, with research subjects from IV grade students and IV grade teachers at SDN 05 V Suku Bawah. In conducting research, data collection techniques and instruments used are interviews, observation, and documentation. The results of the findings in the field indicate the forms of nationalism possessed students in the form of patriotism, self-sacrifice, discipline, unity and integrity, courage and honesty, and discipline and obedience to regulations. The structure of planting an attitude of nationalism can be done in habituation and exemplary activities or contextual examples. The driving and inhibiting factors instilling an attitude of nationalism in students in the form of school facilities, and the limitations of learning media and the delivery of material carried out by teachers.